La réforme pénale et la réciprocité des droits - Pires, Alvaro (Criminologie, 1991)
This letter deals with two major questions. The first shows how the “program” of criminology which emerged in the 19th century contributes to a neutralisation of the impact of discussions concerning human rights in the case of punishment. To do this, the author compares two paradigms of penal reform. The second question tries to clarify the relations established in Quebec between the rights of prisoners and abolitionist alternatives from 1975 on.